Legal Protection by Advocates for The Rights of Suspects in The Investigation Process of Criminal Cases - Umi Enggarsasi (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2023)
In providing legal protection to a suspect, the implementation of Law Number 8 of 1981 concerning Criminal Procedure Law is crucial, especially at the investigation stage in a criminal case. At the interrogation stage, arbitrary actions often occur on the part of investigators against suspects suspected of being involved in criminal acts. This research explores the legal protection of suspects' rights in the process of examining criminal cases, with a focus on the role of advocates in accordance with the provisions of Law Number 8 of 1981 concerning Criminal Procedure Law. The interrogation stage in an investigation often becomes the focal point, where arbitrary actions on the part of investigators can threaten the suspect's rights. This research adopts a library research method with a normative juridical approach. The approach in this research involves library materials or secondary sources, which are then collected, analyzed and researched. Field studies were also carried out to obtain direct data regarding the protection of suspects' rights in the investigation process. The role of advocates in legal assistance at the investigation level has limitations regulated by Article 115 of the Criminal Procedure Code. These restrictions are a step to maintain the smoothness of the investigation process without any interference that could harm the interests of the state. Therefore, apart from advocates having a more passive role at this stage, the principle of legal protection for suspects remains the main focus in running the criminal justice system.